2002
DOI: 10.1093/nar/gkf580
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of TPA induced differentiation in HL-60 cells by DNA microarray analysis

Abstract: The tumor promoter 12-O-tetradecanoylphorbol-13-acetate (TPA) is a potent inducer of differentiation in human promyelocytic leukemia cells. Recently, TPA has been successfully administered to patients with myelocytic leukemia and has produced therapeutic effects that led to temporary remission. These studies demonstrated the potential efficacy of TPA in cancer chemotherapy. We now seek to understand the biological effects and molecular mechanisms of differentiation in response to TPA treatment in leukemia cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 65 publications
2
45
0
3
Order By: Relevance
“…It has been demonstrated that TPA induces the expression of a number of genes that are involved in splicing in particular SC35 (serine/arginine-rich splicing factor 2) and hnRNP A2/B1 (Zheng et al, 2002). Western blot analysis confirmed an induction of hnRNP A2/B1 by TPA (Fig.…”
Section: Identification Of Hnrnp A2/b1 As a Regulator Of Hpv-16 Late mentioning
confidence: 71%
“…It has been demonstrated that TPA induces the expression of a number of genes that are involved in splicing in particular SC35 (serine/arginine-rich splicing factor 2) and hnRNP A2/B1 (Zheng et al, 2002). Western blot analysis confirmed an induction of hnRNP A2/B1 by TPA (Fig.…”
Section: Identification Of Hnrnp A2/b1 As a Regulator Of Hpv-16 Late mentioning
confidence: 71%
“…Expression levels of many genes change with PMA-induced differentiation of HL-60 cells, as demonstrated by using cDNA microarray analysis (29,30). Expression of cell-surface markers whose levels increase (CD11b and CD87) or decrease with differentiation (CD71) were measured by FACS to verify whether differentiation was occurring despite the loss of PDE1B2 and also to begin to characterize the phenotype of the differentiated cell.…”
Section: Pde1b2 Is Not Required For Differentiation But Affects the Fmentioning
confidence: 99%
“…10 The transcript level was reduced by addition of TPA. Microarray analyses of transcription in HL-60 cells examined granulocytic differentiation induced by RA 11 or DMSO, 12 macrophage differentiation induced by TPA, 13 transcript changes induced by vitamin D3 14 and a comparison of transcript level changes induced by RA or by vitamin D3. 15 More recently, transcription in HL-60 and 2 other undifferentiated myeloid leukemia cell lines, K562 and THP1, were compared by RNA-Seq and examination of enriched KEGG pathways.…”
Section: Introductionmentioning
confidence: 99%